Analisis kualitas website Badan Pusat Statistik (BPS) menggunakan metode WebQual 4.0 dan Importance – Performance Analysis (IPA) - Monica Adelya Putri; Kartika Gianina Tileng (AITI, 2021)
The need for data usage in today's era is growing along with the growing interest of researchers and students in doing their assignments. One website that provides reliable statistical data is the Badan Pusat Statistik (BPS). The data searching process requires more time and accuracy. Therefore, the appearance and quality level of a website is considered important factors. A website that is easy for users to understand will greatly help the data search process to be more effective. In this study, the author used WebQual 4.0 and IPA methods by taking researchers who have used the BPS website as this research respondents. Data is collected using online surveys and interview techniques. This study aims to determine the importance level score and the level of performance in the Usability, Information Quality, and Service Quality factors on the BPS website and also map the results of data retrieval into the Cartesian quadrant.